2019
DOI: 10.1111/1468-0009.12436
|View full text |Cite
|
Sign up to set email alerts
|

The Association of State Opioid Misuse Prevention Policies With Patient‐ and Provider‐Related Outcomes: A Scoping Review

Abstract: This scoping review reveals a growing literature on the effects of certain state opioid misuse prevention policies, but persistent gaps in evidence on other prevalent state policies remain. Policymakers interested in reducing the volume and dosage of opioids prescribed and dispensed can consider adopting robust prescription drug monitoring programs with mandatory access provisions and drug supply management policies, such as prior authorization policies for high‐risk prescription opioids. Further research shou… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
56
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
7
2
1

Relationship

0
10

Authors

Journals

citations
Cited by 49 publications
(56 citation statements)
references
References 94 publications
0
56
0
Order By: Relevance
“…This study suggests that PDMP mandates may prevent adolescents from beginning down the path of opioid addiction and IDU, which is important to consider alongside evidence that PDMPs could prompt people who are already using opioids to transition to illicit substances [27]. Enactment of PDMP mandates could complement other evidence-based interventions, such as expanded addiction treatment [44,45], naloxone distribution [46,47], safe prescribing interventions [48], and harm reduction services [49].…”
Section: Plos Medicinementioning
confidence: 95%
“…This study suggests that PDMP mandates may prevent adolescents from beginning down the path of opioid addiction and IDU, which is important to consider alongside evidence that PDMPs could prompt people who are already using opioids to transition to illicit substances [27]. Enactment of PDMP mandates could complement other evidence-based interventions, such as expanded addiction treatment [44,45], naloxone distribution [46,47], safe prescribing interventions [48], and harm reduction services [49].…”
Section: Plos Medicinementioning
confidence: 95%
“…Overdose response after naloxone administration Provision, feasibility and acceptability of naloxone distribution 13 (27.7%) (30,(37)(38)(39)(40)(41)(42)(43)(44)(45)(46)(47)(48) Effectiveness of naloxone and take-home naloxone (THN) for opioid overdose reversal 10 (21.3%) (10,12,(27)(28)(29)(32)(33)(34)(35)31,36) Overdose response after naloxone administration 6 (12.8%) (51,65,66,72,73,75) Naloxone training and education 6 (12.8%) (12,29,33,36,38,45) Recommendations for policy, practice, and gaps in knowledge 4 (8.5%) (67)(68)(69)(70) Naloxone safety (harm and adverse events related to naloxone administration)…”
Section: Reviewmentioning
confidence: 99%
“…Given that research into other legal and policy interventions, such as prescription drug monitoring programs (PDMPs), has shown that the specific components of these interventions may have differential impacts on opioid‐related public health outcomes [5–8], it is likely that research evaluating the effectiveness of specific NAL components may produce more useful results than studies that evaluate NALs as a binary construct. Furthermore, some NAL components may have a differential impact depending on the environment in which they exist.…”
Section: Introductionmentioning
confidence: 99%